Pengaruh Computer Knowledge dan Persepsi Kemudahan Pada Akuntansi Terkomputerisasi dengan Moderasi Pemahaman - Pasaribu, Mhd Husein; Astuty, Widia; Pasaribu, Mhd Hasan; Rahayu, Sri; Suginam, Suginam (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
In this modern era, the use of technology is common and has become a necessity for the wider community This cannot be denied, as technology serves as a means to help humans complete tasks more efficiently and effectively The benefits of technology are also felt by small and medium-sized business owners, especially in their efforts to develop their businesses through the implementation of information technology in their business processes Despite the ease of using technology in financial management, some still prefer traditional financial management methods Through this issue, this research is designed to determine whether computer literacy and perceptions of ease, moderated by accounting understanding, can influence the adoption of computerized accounting by small and medium-sized business owners. The research focuses on UMKM actors domiciled in the city of Medan, specifically in the Medan Denai sub-district, with a total of 84 UMKM respondents The method used in this research is quantitative method with data collection technique in the form of questionnaire distribution The research results obtained through statistical data processing using SmartPLS software version 3.2.9 with partial path analysis technique show that the Perception of Ease variable has a significant positive influence on the implementation of computerized accounting in UMKM organizations with a value of 0.000 (less than 0.05), but the computer understanding variable actually shows a non-significant positive influence with a value of 0.802 (greater than 0.05) on the implementation of computerized accounting. The Accounting Understanding variable also cannot moderate the influence given, whether it is on the computer understanding variable or the perception of ease, with a value of 0.269 (greater than 0.05) for the influence of computer understanding, and 0.173 (greater than 0.05) for the influence of ease perception